Role of Reference group Selection of Medical and Healthcare Services in India: A Cross Sectional Study of Indian Youth - DHYANI , ARCHANA (International Journal of Psychosocial Rehabilitation, 2018)
The healthcare sector in India is vast and diverse, and healthcare-seeking behavior is influenced by a variety of factors, including demographic, socio-economic, and cultural factors. Reference groups, defined as individuals or groups that individuals use as a benchmark for their own behavior and beliefs, have been shown to be important in shaping healthcare behavior in other contexts. However, the role of reference groups in healthcare decision-making among Indian youth has not been extensively studied. Hence, the findings of the study have important implications for healthcare providers and policymakers in India. The study highlights the need for healthcare providers to understand the role of reference groups in shaping healthcare behavior and to develop strategies to effectively communicate with reference groups. Additionally, the study suggests that policymakers should consider the role of reference groups in healthcare decision-making when designing healthcare policies and interventions.